Evidence for a Novel Endometrioid Carcinogenic Sequence in the Fallopian Tube With Unique Beta-Catenin Expression. (March 2020) - Brouwer, Jan; Strickland, Kyle C.; Ning, Gang; Schmelkin, Cindy B.; Kolin, David L.; Hecht, Jonathan; Nucci, Marisa R.; Mourits, Marian J.; Xian, Wa; Crum, Christopher P.
Abstract : Epithelial proliferations in the fallopian tube have been characterized by some as stem cell outgrowths (SCOUTs) and divided into type I and type II. Type II SCOUTs exhibit diffuse cellular beta-catenin nuclear staining (β-catenin + ), implying a CTNNB1 mutation. SCOUTs are more common in perimenopausal and postmenopausal women and are associated with ovarian cancer but have not been linked directly to malignancy. We analyzed type II SCOUTs in various gynecologic conditions, and searched for endometrioid atypical hyperplasias (tubal endometrioid intraepithelial neoplasia) or adenocarcinomas in the tube. β-catenin + SCOUT frequency in cases of neoplasia was 66.7% per case and 30.7% per nonfimbrial cross-section for uterine endometrioid carcinomas versus 25% and 13.3% for controls, respectively ( P =0.02 and 0.09). Multiple (3 or more) β-catenin + SCOUTs in a single section were uncommon; 6 of 9 were associated with a carcinoma or proliferative lesion in the endometrium. Tubal endometrioid intraepithelial neoplasia/atypical hyperplasia displayed complex growth, including focal cribriform growth patterns and squamous morules. Two cases of type II SCOUTs associated with tubal endometrioid intraepithelial neoplasia/atypical hyperplasia and/or adenocarcinomas in the fallopian tube were identified, both of which coexisted with a separate endometrioid adenocarcinoma, one with bilateral ovarian endometrioid adenocarcinomas. Both benign and neoplastic tubal lesions were β-catenin + . This report is the first to link components of a unique β-catenin + endometrioid carcinogenic sequence in the fallopian tube. It further emphasizes the multifocal nature of endometrioid neoplasia in the female genital tract and poses questions regarding the frequency and biologic underpinnings of β-catenin + proliferations in the oviduct. Abstract : Supplemental Digital Content is available in the text.